2016
DOI: 10.1002/anie.201602611
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Biosynthetic Pathway of the Ribosomally Synthesized and Post‐translationally Modified Peptide Ustiloxin B in Filamentous Fungi

Abstract: The biosynthetic machinery of the first fungal ribosomally synthesized and post-translationally modified peptide (RiPP) ustiloxin B was elucidated through a series of gene inactivation and heterologous expression studies. The results confirmed an essential requirement for novel oxidases possessing the DUF3328 motif for macrocyclization, and highly unique side-chain modifications by three oxidases (UstCF1F2) and a pyridoxal 5'-phosphate (PLP)-dependent enzyme (UstD). These findings provide new insight into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 24 publications
1
72
1
Order By: Relevance
“…In contrast, in the present study, successful biotransformation was observed in the A. oryzae transformant without coexpression of CYP and CPR; this indicates that the intrinsic CPR (Ao‐CPR) in A. oryzae is functional to CYPs from basidiomycete fungi, although only two CPRs are found in the genome . Notably, Ao‐CPR also mediates electron transfer to CYPs from several ascomycete fungi, such as Aspergillus , Alternaria , Bipolaris , Chaetomium , and Phoma species, which suggests that Ao‐CPR is a versatile redox partner for fungal CYPs.…”
Section: Methodscontrasting
confidence: 83%
See 1 more Smart Citation
“…In contrast, in the present study, successful biotransformation was observed in the A. oryzae transformant without coexpression of CYP and CPR; this indicates that the intrinsic CPR (Ao‐CPR) in A. oryzae is functional to CYPs from basidiomycete fungi, although only two CPRs are found in the genome . Notably, Ao‐CPR also mediates electron transfer to CYPs from several ascomycete fungi, such as Aspergillus , Alternaria , Bipolaris , Chaetomium , and Phoma species, which suggests that Ao‐CPR is a versatile redox partner for fungal CYPs.…”
Section: Methodscontrasting
confidence: 83%
“…In recent years, we have successfully elucidated the biosynthetic pathways for natural products, such as di‐ and sesterterpenes (aphidicolin, ophiobolin, sesterfisheric acid), indolediterpenes (paxilline, aflatrem, penitrem, and shearinine), polyketides (betaenone and didymellamide B), and ribosomal peptide (ustiloxin), by harnessing the biosynthetic machinery in A. oryzae . Artificial reconstitution of the biosynthesis allowed us to isolate biosynthetic intermediates of these natural products.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro assays with UstF1, which co-purified with FAD, resulted in the conversion of 240 to 51 , thus demonstrating that UstF1 is involved in sulfoxide formation in 51 biosynthesis (Scheme 58). 571 Based on the known modes of reactivity of flavin monooxygenase, it seems plausible that S -oxygenation of 240 involves attack of the nucleophilic S atom on the electrophilic distal oxygen of a flavin C 4a -hydroperoxide intermediate.…”
Section: S–s S–o and S–n Bond Forming Enzymesmentioning
confidence: 99%
“…The ability of phallotoxins, such as phalloidin 25, to bind actin filaments with a high affinity was used extensively to study cell biology, and phalloidin staining is still considered a gold standard for actin localisation in cells [47,48]. Ustiloxins 26-31 (Figure 3) were not originally identified as RiPPs when they were first isolated from the rice pathogen Ustilaginoidea virens, but the elucidation of their biosynthetic pathway has led to the reclassification of these metabolites as RiPPs [49]. Ustiloxins inhibit the assembly of microtubules during cell division, resulting in antimitotic properties and cytotoxicity against various cancer cells lines, including stomach, lung, breast, colon and kidney cancer cells [50].…”
Section: Ribosomally Synthesised and Post-translationally Modified Pementioning
confidence: 99%